Health care as a worldwide concern. Insights on the Italian and Indian health care systems and PPPs from a VSA perspective. Issue 2 (1st July 2014) - Saviano, Marialuisa; Parida, Ratri; Caputo, Francesco; Kumar Datta, Saroj
Abstract : Purpose: – Health is a fundamental populations' need and an integral part of the socio-economic development of a country. However, it is required to explain the growing role of the private sectors in addressing various health care needs. The purpose of this paper is to analyse potential contribution, criticalities and conditions of success of public-private partnership (PPP) as a strategy to face the complexity of nationally relevant Italian and Indian service systems. Design/methodology/approach: – The methodology is built upon the basis of the viable systems approach (VSA) integrated with the fundamental interpretative elements of service science and service-dominant logic to contextualize interpretation to the management of service systems benefitting from recent advances in these research fields. Findings: – A VSA-based general framework of reference is built that is useful for analysing any relational context in which different aims and expectations need to be harmonized to make the collaboration effective. On the basis of this framework, first insights on Italian and Indian health care PPPs are proposed, highlighting key elements of analysis and criticalities that may challenge a positive conclusion on health care PPPs. Practical implications: – The implications of the study are both theoretical and practical. From a theoretical perspective, the study contributes to the scholarly understanding of complex health care system in Italy as well as in India with particular reference to the public-private collaboration phenomenon. It also suggests theoretical approaches in the form of a generic VSA-based framework as applicable. From a practical perspective, the study stimulates managers to a critical reflection about current health care management approaches which are reflected in the adoption of PPPs solutions. Originality/value: – The paper discusses relevant worldwide decision-making challenges, such as the equality in the populations' access to health service, suggesting managers the way to create conditions of consonance among the diverse stakeholders for a successful health care PPPs.